2012
DOI: 10.9799/ksfan.2012.25.4.787
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Proper D-Xylose Concentration in Sugar Mixture to Reduce Glycemic Index (GI) Value in the Human Clinical Model

Abstract: The objective of this study was to investigate the proper concentration of D-xylose which is expected to reduce the GI (Glycemic index) value of sucrose in the human body. When subjects took a sucrose mixture containing 5% and 10% D-xylose, the blood glucose levels were lowered by approximately 27.5% and 25.9%, respectively, compared to those of sucrose. The GI values of sucrose mixtures containing 5% and 10% D-xylose were 49.3 and 50.4, respectively. The reduction in GI value was not dependent on the D-xylose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In a previous study, sucrose mixtures containing 5% and 10% D-xylose were associated with significant blood glucoselowering effects in humans [57]. In another study, administration of sucrose solution containing 10% D-xylose exhibited significantly lower under the glucose curve values as well as under the insulin curve values, in an oral glucose tolerance test completed by healthy individuals [22].…”
Section: Discussionmentioning
confidence: 96%
“…In a previous study, sucrose mixtures containing 5% and 10% D-xylose were associated with significant blood glucoselowering effects in humans [57]. In another study, administration of sucrose solution containing 10% D-xylose exhibited significantly lower under the glucose curve values as well as under the insulin curve values, in an oral glucose tolerance test completed by healthy individuals [22].…”
Section: Discussionmentioning
confidence: 96%
“…A recent study showed that the administration of 5% or 10% d -xylose in sucrose mixtures significantly lowered blood glucose levels in humans [45]. Furthermore, administration of 10% d -xylose in a sucrose solution significantly reduced under the glucose curve (AUCg) values and under the insulin curve (AUCi) values obtained from OGTTs performed for healthy individuals [46].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies examined whether sucrose drinks with 5 % (w/w) D-xylose exerted beneficial effects on enhancing the glycemic response [ 18 , 19 ], but the number of subjects in these studies was too small (n = 10 and n = 13) to define the effect of D-xylose.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of D-xylose occurs via the inhibition of sucrase activity in a non-competitive manner [ 12 ]. Specifically, D-xylose inhibits sucrase activity by combining with the intermediate of sucrase and glucose, immediately after the dissociation of fructose [ 18 ].…”
Section: Discussionmentioning
confidence: 99%